EP1332 Follow the yellow brick road – Supra-renal para-aortic lymphadenectomy for metastatic ovarian cancer. (1st November 2019) - Daia, MT; Chandrasekaran, D; Lawrence, A; Brockbank, E; Manchanda, R; Jeyarajah, A; Phadnis, S
Abstract : Introduction/Background: Complete cytoreduction along with platinum sensitivity are the most important prognostic factors in advanced ovarian cancer. Cytoreductive surgery should include excision of enlarged lymph nodes in order to achieve R0 resection. Although pelvic, inguinal and infra-renal para-aortic lymphadenectomy (PALND) is commonplace in gynae-oncological surgery, there is limited literature on supra-renal PALND. We aim to present in this video the advantages, challenges and superior exposure of the upper abdominal aorta when approaching from the left side, as presented in this video. Methodology: Real-time video of PALND from above the renal vessels to the bifurcation of the aorta was recorded. This was performed at the time of primary cytoreductive surgery for clinical stage 3c ovarian cancer with involvement of para-aortic nodes above the renal vessels. Descending colon was mobilised up to the splenic flexure in order to expose the left kidney and the aorta. The duodenum was reflected off the left kidney. From the pelvis, the left ovarian vessels were identified and lateralizing along with the ureter, enabling identification and exposure of the renal vessels with ease. Enbloc excision of enlarged nodal tissue undertaken with harmonic focus. Results: This video demonstrates the left side surgical approach which enables superior exposure of high Para aortic nodes. Following the ovarian vessels enables easy and safe identification and exposure of renal vessels. Conclusion: Supra renal PALND should not be an obstacle in achieving complete cytoreduction in women with ovarian cancer and the left side approach enables better exposure compared to the right-sided classic approach. Moreover, this video adds valuable teaching resource to the current limited reports of this surgical approach in ovarian cancer. Disclosure: Nothing to disclose